IMPLEMENTASI PELIMPAHAN SEBAGIAN WEWENANG BUPATI KEPADA CAMAT DALAM LAYANAN PERIZINAN BIDANG KESEHATAN DI KECAMATAN MARGAHAYU KABUPATEN BANDUNG (Studi Kasus pada Layanan Perizinan Depot Isi Ulang Air Minum Mineral)1 - Iwan Kurniawan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
The objective of this research is to understand the implementation of partial delegation of Regency Head's authority to.Sub-District Head in providing license on Health Affairs in the Margahayu Sub-District, Regency of Bandung, particularlyfor licensing on depot for mineral water replenishment. Based on the research result, it is known that the licensing service on.the depot for mineral water replenishment has not been able to be implemented yet, therefore it has no impact on goal.attainment of authority delegation which is to bring nearer the service access and to improve the quality of service and.working performance marked by the absence of capacity enhancement of the sub-district personnel. Meanwhile, the existing problems can be categorized as follow: 1) Lack of technical support; 2) The unavailability of financial resources and 3) Limitation on Administrative Capacity.